A comparison study on combustion and emission characteristics of actual synthetic gas mixtures. (1st March 2020) - Yilmaz, Harun; Cam, Omer; Yilmaz, Ilker
Highlights: A swirl stabilized premixed burner was designed and manufactured. Two actual synthetic gas mixtures were combusted under the same conditions. Combustion and emission characteristics of such mixtures were compared. 61.9%H2 -26.2%CO-6.9%CH4 -5.0%CO2 mixture performed better in terms of emissions. Abstract: In this study, combustion and emission characteristics of output synthetic gas mixtures of two different power stations, namely Schwarze Pumpe and Fife, were investigated in a swirl stabilized combustor. For this purpose, an experimental test rig which is equipped with a premixed burner that can combust synthetic gases in a wide gas composition range was built and utilized. Tested synthetic gas mixtures are 61.9%H2 -26.2%CO-6.9%CH4 -5.0%CO2 (Schwarze Pumpe - H2 /CO: 2.36) and 34.4%H2 -55.4%CO-5.1%CH4 -5.1%CO2 (Fife - H2 /CO: 0.62). Actually, these gas mixtures contain slight amount of N2 and Ar. Therefore, right amount of CO2 was added to each mixture to represent these inert constituents. The comparison of combustion behavior of respective synthetic gas mixtures was conducted via examining axial and radial temperature values throughout the combustor. Besides, emission behavior was interpreted by analyzing measured CO, CO2 and NO values at combustor chimney. Results of this study showed that 61.9%H2 -26.2%CO-6.9%CH4 -5.0%CO2  mixture performs better in respective combustor with regard to temperature distribution, and emitted CO and NO levels.